2022
DOI: 10.1002/ehf2.14121
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometric parameters‐derived estimation of muscle mass predicts all‐cause mortality in heart failure patients

Abstract: Aims Reduction in appendicular skeletal muscle mass index (ASMI) assessed by dual‐energy X‐ray absorptiometry (DEXA) has been shown to be independently associated with a higher mortality rate in patients with heart failure (HF). However, DEXA is not suitable for measurement of muscle mass in a daily clinical setting and in large population‐based studies. The aim of this study was to determine whether ASMI predicted from anthropometric indicators (predicted ASMI) serves as an alternative to DEXA‐measured ASMI f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 20 publications
1
11
0
Order By: Relevance
“…Evidence on the prognostic impact of ASMI, defined by Anthropometric and Predicted models, is scarce in patients with heart failure. A retrospective study enrolling 539 patients with heart failure revealed that a low Predicted‐ASMI was significantly associated with all‐cause mortality and provided additional prognostic value to pre‐existing risk factors 16 . However, the prognostic impact of sarcopenia assessed using the Predicted‐ASMI has not yet been investigated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Evidence on the prognostic impact of ASMI, defined by Anthropometric and Predicted models, is scarce in patients with heart failure. A retrospective study enrolling 539 patients with heart failure revealed that a low Predicted‐ASMI was significantly associated with all‐cause mortality and provided additional prognostic value to pre‐existing risk factors 16 . However, the prognostic impact of sarcopenia assessed using the Predicted‐ASMI has not yet been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the Predicted model, which was calculated using sex, weight, calf circumference (CC), and mid‐arm circumference (MAC), showed excellent correlation with DEXA‐measured ASM in patients with heart failure 15 . ASM measured using the Predicted model was associated with all‐cause mortality in patients with heart failure 16 . However, whether sarcopenia is evaluated using Anthropometric or Predicted models has not been directly compared with that diagnosed using the gold standard method, DEXA, in older patients with heart failure.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Sarcopenia, that is, a decline in skeletal muscle mass and function, has been shown to be an age‐dependent phenomenon, but aging is not the sole mechanism of sarcopenia, and various pathological conditions, including HF, play pivotal roles in the promotion of muscle wasting 12 . Results of recent studies, including our previous study, showed that the presence of muscle wasting is a powerful and independent predictor for mortality in patients with HF 13–16 . Thus, sarcopenia is a useful marker of poor clinical outcome in HF patients.…”
Section: Introductionmentioning
confidence: 87%
“…12 Results of recent studies, including our previous study, showed that the presence of muscle wasting is a powerful and independent predictor for mortality in patients with HF. [13][14][15][16] Thus, sarcopenia is a useful marker of poor clinical outcome in HF patients. Furthermore, the results of a pioneering study by Anker et al showed that weight loss of ≥6% after inclusion in the study was a strong predictor of impaired survival in HF patients.…”
Section: Introductionmentioning
confidence: 99%